PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Ahmad Faiz Falahudin; Noor Shodiq Askandar; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study was conducted to determine the effect of competence and independence on audit quality with auditor ethics as a moderating variable. This research was conducted at several Public Accounting Firms (KAP) in Gresik City. The data collection method used in this study was to distribute questionnaires to respondents in the form of written questions. The sample used in this study is a public accounting firm that has been established in several areas in Gresik City and a public accounting firm that is willing to be surveyed. This study uses 43 respondents who work at several Public Accounting Firms in Gresik City. The data analysis method used in this study used multiple linear regression analysis. The results of this study indicate that the competence and independence variables have a positive effect on audit quality. The variable of auditor ethics as moderating indicates that auditor ethics moderates the relationship between competence and audit quality. Auditor ethics as moderating variable shows that auditor ethics does not moderate the relationship of independence to audit quality. Keywords: Competence, independence, audit quality and auditor ethics